Cork hygroscopic equilibrium moisture content (European Journal of Wood and Wood Products, 1998)
This work is related to the establishment of the curves of cork moisture content in hygroscopic equilibrium (HEM curves), which allow to predict the moisture content of cork planks, one of the most important parameters in cork trading and processing. HEM curves for 20 ~ and 40 ~ based on an empirical model related to experimental data, were mathematically treated in order to set a series of curves in steps of 5 ~ These curves were transformed in a more usual display of the hygroscopic equilibrium mois- ture content, for the most common temperature and hu- midity ranges and tested against experimental data using two cork types.